The Important Role of Social Media in Improving the Performance of Law Enforcement Apparatus in Indonesia - Ramadhani, Milenia (Journal of Legal and Cultural Analytics, 2024)
The very rapid development of the number of Internet and social media users in Indonesia is affecting all communication and interaction spaces in society. One of them can be a strength in controlling the performance of law enforcement officials. This article attempts to explain the important role of social media in efforts to improve the performance of law enforcement officials in Indonesia. The method used in this research is qualitative research on empirical law with data collection techniques carried out by literature study. The results of the research show that the important role of social media in efforts to improve the performance of law enforcement officials includes as a fast disseminator of information, as advocacy and support for certain cases, as a public pressure provider on officials and the government, exposing cases that are not exposed by conventional media, as media for monitoring accountability and transparency, and as a place for inclusive discussion and debate. The important role of social media should not be overshadowed by the negative impacts of social media such as societal polarization, unequal access, hoaxes and fake news, intimidation and verbal violence. Therefore, anticipation is needed such as digital literacy, social media regulations, education and awareness as well as increasing empathy and sympathy using social media.